2016
DOI: 10.1080/19371918.2015.1099494
|View full text |Cite
|
Sign up to set email alerts
|

Nativity and Health Disparities: Predictors of Immigrant Health

Abstract: This study examines the differences in the social determinants of health and chronic health conditions of immigrants and nonimmigrants. The logistic regression results indicate that employment, education, poverty, residential status, and neighborhood safety have strong influence on the health of immigrants and native-born Americans; however, gender and place of residence are significant to only nonimmigrant health. For chronic health conditions, age and employment status are significant predictors for immigran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(17 reference statements)
0
8
1
Order By: Relevance
“…Income was a common factor in reducing health inequalities in urban and rural areas in our study. In previous studies, income was often found to be associated with health and high-income groups tended to report good health [7, 12, 36, 51]. Zhou et al [52] using data from the Chinese NHSS conducted in 2003 and 2008, reported strong pro-rich inequity in access to inpatient utilization in rural China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Income was a common factor in reducing health inequalities in urban and rural areas in our study. In previous studies, income was often found to be associated with health and high-income groups tended to report good health [7, 12, 36, 51]. Zhou et al [52] using data from the Chinese NHSS conducted in 2003 and 2008, reported strong pro-rich inequity in access to inpatient utilization in rural China.…”
Section: Discussionmentioning
confidence: 99%
“…There were demographic characteristics [7], socioeconomic status [36], lifestyle factors [11] and home environment [37]. Gender, age, ethnicity, marital status, place of residence and household size were included in demographic characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Disparities in neurodevelopment have been described in children with different socio-demographic indicators [ 1 , 2 , 3 ]. Children in communities of color, immigrant and low-income families have been shown to be at high risk for adverse health and developmental outcomes [ 1 , 2 , 3 , 4 , 5 , 6 ]. Immigrant health is of particular interest due to the increasing influx of global migration, including within the United States (US).…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in neurodevelopment have been described in children with different socio-demographic indicators [1][2][3]. Children in communities of color, immigrant and lowincome families have been shown to be at high risk for adverse health and developmental outcomes [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Health is influenced by a complex interplay of individual factors, including genetics, lifestyle, ethnicity, and social determinants such as immigrant status [ 21 ]. In fact, Hispanic women could have an increased risk of developing GDM [ 22 ] due to both genetic predisposition and lifestyle habits [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%